Konsep Pendidikan Islam dalam Kitab Ta'lim al-Muta'allim Karya Al-Zarnuji serta Implementasinya dalam Konteks Pendidikan Islam - Atikah Salma Hidayati; Fauzan Huda Perdana; Ilma Hasanah; Muhamad Azhar Ibrahim; Achmad Faqihuddin; Syahidin Syahidin (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This article discusses the concepts of Islamic education contained in the book Ta'lim al-Muta'allim-Tariq at-Ta'allum by Sheikh Al-Zarnuji and its implementation in the context of Islamic education. This article begins with an explanation of the meaning of the concept and Islamic education. The concepts of Islamic education discussed include the objectives of Islamic education, the curriculum of Islamic education, the characteristics of teachers, the characteristics of students, learning manners, and learning methods. An explanation of the implementation of these concepts of Islamic education in the context of contemporary Islamic education is also discussed in this article. Overall, this article provides a comprehensive understanding of the concepts of Islamic education contained in the book Ta'lim al-Muta'allim-Tariq at-Ta'allum by Sheikh Al-Zarnuji and their implications in the practice of Islamic education today.